Child migration and educational progression in the Savannah regions of Ghana - Tamanja, Emmanuel M. J. (Technische Universität Dortmund, 2014)
Child migration in Ghana has moved beyond the concerns of individual child migrants and their families, to one of national development concerns. Streets, pavements and other public spaces in the cities and towns - especially Accra - are flooded with children engaged in various activities. These children are not only a nuisance to road users and city authorities, but exert pressure on social amenities as well as threat to security. However, little is known about the education of children when they migrate. This requires research attention, to shed light on the phenomenon. In this study, I explore the motivations for migration of children from Bongo district to Accra in Ghana and examine how migration influences their pursuit of basic education. The study employed a mixed methods design involving observation, interviews with 35 child migrants, community discussions, interviews with experts and schedule officers of government and non-governmental organisations working on issues of child migration. Furthermore, questionnares were administred to 490 (250 migrant and 240 non-migrant) children in 10 schools in the district and their academic performance data obtained and analysed, using Mann-Whitney U Test, to find differences in their performance. Poverty, peer influence and pursuit of education emerged as major motivational factors, while non-migrant school children performed relatively better than their migrant counterparts. Nevertheless, the overall effects of migration on education was found to be mixed. Whereas it was negative or positive for some, others pursued apprenticeship as an alternative. I conclude that children in deprived regions migrate to escape unfavourable living conditions and to accumulate wealth in urban areas. However, involvement in migration has negative effects on performance in class with the likelihood of stalling progress in education. Furthermore, I recommend affirmative action by national and local government actors, in order to reduce poverty in rural areas while confronting the daunting challenges in rural schools to improve access and quality.
Implications for planning and spatial development
Keywords: Migration; Planning and development; 710